Análise da integração dos stakeholders na adoção de estratégias de marketing verde: um estudo em empresa moveleira - Brandão, Marcelle Rossi de Mello (2009)
This master's thesis aims to ascertain how the Stakeholders interactions influence the adoption of green marketing strategies from the perspective of the Alpha Company, a furniture industry located in Rio Grande do Norte, Brazil. The methodology has a qualitative approach and uses the exploratorydescriptive case study method as model of formal and systematic study. Following the theoretical and conceptual propositions of Polonsky (1995), Michell, Angle and Wood (1997) and Frooman (1999) as a reference base. This study identifies and assesses the importance degree of the relevant stakeholders, shows their expectations and needs and describes the tactics used by the company for the implementation of green marketing strategies. The study describes the reality of a furniture industry in Rio Grande do Norte, and shows his philosophy and background; identifies present stakeholders that influence the decision process of the company and also, analyzes the degree of importance of each group showing their needs and expectations and, finally, it states the changes in the organization with the implementation of green marketing strategies. The results it s concluded that stakeholders are taken into consideration in the adoption of green marketing strategies, even without a proper strategic perception from the company, an imperative to advance towards the adoption of the green marketing philosophy. This case study explores knowledge that may be used and suited to small companies that act in the strategic segment-trend of green marketing